A comparative analysis of colorative idioms used in Kazakh and Japanese - Beiil, Y.; Saudanbekova, Sh. (Journal of Oriental Studies, 2023)
This article deals with the everyday use of colorative idioms in the Kazakh and Japanese languages. The article analyses Japanese idioms and considers ways of their comparison with Kazakh idioms. There are different variants of some phrases for comparison. The article also draws attention to the fact that the cultural heritage of idioms is described in relation to the specifics of the nation. Some of the phrases mentioned in the article can be useful for effective text translation. There are many elements of cultural identity in everyday speech, but translation can be problematic. Solving these problems is not easy and requires a lot of work and talent. This can easily be seen in idioms expressing the customs, social life and habits of a particular nation. Translation and replacement of phrases not only requires a special approach, but also the ability to pick out these phrases from thousands of words. Moreover, finding an analogue in another language is a very difficult process. In the following article the author focuses on the translation of phrases.